Involvement of Manduca sexta peptidoglycan recognition protein-1 in the recognition of bacteria and activation of prophenoloxidase system - Sumathipala, Niranji (2010)
Although the importance of peptidoglycan recognition proteins (PGRPs) in detecting bacteria and promoting immunity is well recognized in Drosophila melanogaster and other insect species, such a role has not yet been experimentally established for PGRPs in the tobacco hornworm, Manduca sexta. In this study, we purified M. sexta PGRP1 from the baculovirus-insect cell expression system, tested its association with peptidoglycans and intact bacteria, and explored its possible link with the prophenoloxidase activation system in larval hemolymph. Sequence comparison suggested that PGRP1 is not an amidase and lacks residues for interacting with the carboxyl group of meso-diaminopimelic acid-peptidoglycans (DAP-PGs). M. sexta PGRP1 gene was constitutively expressed at a low level in fat body, and the mRNA concentration became much higher after an injection of Escherichia coli. Consistently, the protein concentration in larval plasma increased in a time-dependent manner after the immune challenge. Purified recombinant PGRP1 specifically bound to soluble DAP-PG of E. coli but not to soluble Lys-type PG of Staphylococcus aureus. In addition, this recognition protein completely bound to insoluble PGs from Micrococcus luteus, Bacillus megaterium and Bacillus subtilis, whereas its association with the bacterial cells was low even though their peptidoglycans are exposed on the cell surface. After PGRP1 had been added to plasma of naïve larvae in the absence of microbial elicitor, there was a concentration-dependent increase in prophenoloxidase activation. Phenoloxidase activity, as usual, increased after the plasma was incubated with peptidoglyans or bacterial cells. These increases became more prominent when insoluble M. luteus or B. megaterium PG or soluble E. coli PG and PGRP1 were both present. Statistic analysis suggested a synergistic effect caused by interaction between PGRP1 and these PGs. Taken together, these results indicated that PGRP1 is a member of the M. sexta prophenoloxidase activation system, which recognizes peptidoglycans from certain bacteria and initiates the host defense response. The unexplained difference between the purified PGs and intact bacteria clearly reflects our general lack of understanding of PGRP1-mediated recognition and how it leads to proPO activation.